2020
DOI: 10.11604/pamj.2020.36.159.21239
|View full text |Cite
|
Sign up to set email alerts
|

Influenza epidemiology and risk factors for severe acute respiratory infection in Morocco during the 2016-2017 and 2017/2018 seasons

Abstract: Introduction in order to implement an influenza vaccination program for high-risk-groups in Morocco, as recommended by the World Health Organization, an epidemiological study indicating the influenza virus effect in the development of complicated influenza for subjects with co-morbidity was required. The present study aims to evaluate the risk factors for severe acute respiratory infections caused by influenza in risk groups. Methods this research is based on the epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…In the Before-2020 group, male sex was more prone to severe disease and ICU admittance. Similarly, in studies performed before COVID-19 by Martinez et al [12], and Ezzine et al [18], male sex was more prevalent among hospitalized patients and patients who died.…”
Section: Discussionmentioning
confidence: 76%
“…In the Before-2020 group, male sex was more prone to severe disease and ICU admittance. Similarly, in studies performed before COVID-19 by Martinez et al [12], and Ezzine et al [18], male sex was more prevalent among hospitalized patients and patients who died.…”
Section: Discussionmentioning
confidence: 76%
“…Higher positivity in patients with SARI compared to those with ILI except for age group ≥ 15 to < 45 years old. This variation has been demonstrated in many studies with some differences; study in Morocco showed highest positivity rates among ≥ 65 years of SARI patients compared to 5–15 years of ILI patients [ 25 ]. Study conducted in Egypt reported similar positivity among < 15 years, increase in the positivity in SARI and decrease in ILI patients ≥ 15 years old [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…The multivariate analysis of this study identified risk factors for hospitalization of severe influenza-associated SARI including extremes age < 5 and ≥ 65 years and three comorbidities: diabetes, heart disease and chronic respiratory disease. These risk factors have been founded in several studies conducted in developing and developed countries [ 25 , 33 35 ]. As well as, they were within the risk group to whom WHO recommended influenza vaccination [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes have been linked to the IFN cascade and are correlated with increased type I IFN levels. Both type I and III IFN signaling were similarly found to hinder clearance of S. aureus from the nasopharynx in the context of superinfection [ 36 ]. Type I IFNs are involved in the formation and activation of the inflammasome, the subsequent activation of caspase-1 and generation of the proinflammatory cytokines interleukin 1β (IL-1β) and interleukin 18 [ 83 ].…”
Section: Antibiotic Properties Of Nasal Microbiome and Impacts On Local Immune Responsementioning
confidence: 99%